Analysis of proteins associated with the expression of cyclooxygenase-2 and the biosynthesis of PGE2 in breast cancer cells with different metastatic potential - V. E. Shevchenko; M. A. Taipov; S. V. Kovalev; N. E. Arnotskaya; O. M. Pavlova; I. A. Kudryavtsev; Z. N. Nikiforova (Опухоли женской репродуктивной системы)
The proteome of lysates of the breast tumor cell lines MCF-7, BT-474, and ZR-75-1 was mapped, resulting in the sequence of 340 proteins. The proteins associated with the biosynthesis of PGE2 and with the regulation of cyclooxygenase-2 expression were identified and their relative expression levels were determined. Potential goals for the targeted therapy of breast cancer, such as prostaglandin E2 and D2 receptors, pros- taglandin E synthase, 15-hydroxyprostaglandin dehydrogenase and leukotriene-A4 -hydrolase, are of special interest in this group.